Zależność pomiędzy płynnością, rentownością i upadłością firm. Wyniki badań empirycznych dla polskich spółek giełdowych - Wyrobek, Joanna (Relationship Between Liquidity, Profitability and the Risk of Bankruptcy, Empirical Evidence for Polish Stock Companies, 2007)
The article explores the relationship between liquidity, profitability and risk of bankruptcy of the firm, trying to assess the efficiency of different working capital financing strategies. Empirical evidence suggests that in Polish conditions firms should lean towards adopting a conservative strategy because there is no negative relationship between liquidity and profitability and there is a positive relationship between liquidity and the risk of bankruptcy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 664-675